MiR-200b is upregulated in plasma-derived exosomes and functions as an oncogene by promoting macrophage M2 polarization in ovarian cancer - Jun Xiong; Xiaoju He; Yuanyuan Xu; Wei Zhang; Fen Fu (BMC, 2021)
Abstract Background Ovarian cancer is the seventh most common cancer in women and the second most reason of gynecologic cancer-related death. Growing evidence showed that exosomal miRNA plays a crucial role in the progression of ovarian cancer. Methods Exosomes were identified using nanoparticle tracking analysis, transmission electron microscopy and marker proteins detection. The levels of mRNA and proteins were ensured by qRT-PCR and western blot, respectively. Immunofluorescence, flow cytometry and ELISA assay were carried out to analyze macrophages polarization. CCK-8 and Transwell assay were used to measure the cell viability and invasion of ovarian cancer cells. The interaction of miR-200b and Kruppel like factor 6 (KLF6) was ensured by using luciferase reporter assay. Results Here, we obtained plasma-derived exosomes successfully, and proved that miR-200b was increased in the exosomes of ovarian cancer patients. Subsequently, our data showed that increasing of miR-200b could promote macrophage M2 polarization, but inhibit M1 polarization. miR-200b-overexpressed macrophages-conditioned medium notably enhanced the cell viability and invasion of ovarian cancer cells. Moreover, increasing of miR-200b inhibited KLF6 expression, while decreasing of miR-200b promoted KLF6 expression. Overexpression of KLF6 recused miR-200b-induced macrophage polarization toward M2, and the inhibitory effect of miR-200b on M1 polarization. Conclusions Overall, our results demonstrated that miR-200b was highly expressed in the plasma-derived exosome of ovarian cancer patients, and promoted the proliferation and invasion of ovarian cancer cells through inducing macrophage M2 polarization by suppressing KLF6 expression. Our results suggested that miR-200b might be a novel target for ovarian cancer treatment.